Prestasi Akademik Mahasiswa Fakultas Ilmu Pendidikan UNIMED Ditinjau dari Kecerdasan Majemuk dan Karakter Belajar. - Chairin Nur Syahda; Cindy Novria; Miftahul Azra Aqin Siregar; Resky Febrina Tarigan; Yani Sitepu; Yolanda Fahel Silitonga (CV. Eracita Grup, 2026)
This study aims to describe the academic achievement of students at the Faculty of Education, Universitas Negeri Medan, viewed from multiple intelligences and learning character. This research employed a quantitative approach with a descriptive research design. The participants consisted of 25 students from several study programs selected using a saturated sampling technique. Data were collected through a closed-ended questionnaire that measured aspects of multiple intelligences, learning character, and academic achievement. The data were analyzed using descriptive statistical techniques, including mean scores, percentages, and frequency distributions. The results indicate that students possess diverse profiles of multiple intelligences and learning character, which contribute differently to their academic achievement. Students who demonstrate well-developed multiple intelligences supported by positive learning character tend to show better academic performance. These findings emphasize the importance of implementing a holistic educational approach that integrates cognitive abilities and character development to enhance students’ academic achievement. This study is expected to provide insights for educators and higher education institutions in designing learning strategies that accommodate students’ diverse potentials.